Coronary heart disease and gut microbiota: A bibliometric and visual analysis from 2002 to 2022 - Long, Dan; Mao, Chenhan; Zhang, Xinyue; Liu, Yaxuan; Shangguan, Xueli; Zou, Menglong; Zhu, Ying; Wang, Xindong (Frontiers in Cardiovascular Medicine, 2022)
Background: Existing studies have indicated that gut microbiota is closely related to the occurrence and development of coronary heart disease(CHD). Gut microbiota and its metabolites may be important diagnostic markers for CHD in the future and are expected to become new targets for the prevention and treatment of CHD. However, the current studies exploring the link between CHD and gut microbiota are miscellaneous and poorly targeted, without bibliometric analysis available. Objective: The purpose of this research was to perform a bibliometric and visual analysis of published papers on the relationship between CHD and gut microbiota. The study also sought to identify principal authors, institutions, and countries to analyze the research status and trends of gut microbiota research in the field of CHD. Methods: The Web of Science Core Collection (WOSCC) database was searched for publications on CHD and gut microbiota between 2002 and 2022. CiteSpace 5.8. R1, VOSviewer 1.6.16, and Microsoft Excel 2019 software tools were utilized to perform this bibliometric analysis and visualization. Results: There were 457 qualified publications found in total, with the annual number of publications increasing. The United States dominated in this field. Hazen, Stanley l was the author of the most papers. Cleveland Clinic published the most papers of any institution. The six main clusters' specific characteristics were discovered through analysis of the co-occurrence of keywords: inflammation, diet, trimethylamine n-oxide, metabolism, cardiovascular disease, and myocardial infarction. Newly emerging research has focused predominantly on gut microbiota metabolites and recent strategies for intervention in coronary atherosclerosis. Conclusion: These results provided a useful perspective on current research and future prospects for the research on the link between CHD and gut microbiota, which may help researchers to select suitable collaborators and facilitate their research to elucidate the underlying molecular mechanisms of CHD, including the causes, prevention, and treatment.